2007
DOI: 10.1094/cchem-84-5-0518
|View full text |Cite
|
Sign up to set email alerts
|

Protein Digestibility of Selected Legumes Treated with Ultrasound and High Hydrostatic Pressure During Soaking

Abstract: In vitro protein digestibility (IVPD) of lentils, chickpeas, peas, and soybeans treated with ultrasound or high hydrostatic pressure (HHP) during soaking and then heated for 30 min at 98°C was determined using the three‐enzyme method (trypsin, chymotrypsin, and peptidase). The IVPD of raw legumes ranged from 72% for soybeans to 83% for dry green peas. The increase in the IVPD after soaking was observed in lentils but not in other legumes. Heating increased the IVPD of the tested legumes by 2–13%. While the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 30 publications
0
22
3
Order By: Relevance
“…However, our results are in conflict with several previous studies which shown that the ultrasound treatment of various proteins did not significantly alter the overall DH or the effects were minimal [43,44]. In this light, Lei et al [27] showed that the sonication of ovotransferrin before thermolysin hydrolysis had insignificant effect on its digestibility.…”
Section: Resultscontrasting
confidence: 99%
“…However, our results are in conflict with several previous studies which shown that the ultrasound treatment of various proteins did not significantly alter the overall DH or the effects were minimal [43,44]. In this light, Lei et al [27] showed that the sonication of ovotransferrin before thermolysin hydrolysis had insignificant effect on its digestibility.…”
Section: Resultscontrasting
confidence: 99%
“…Dther studies on Brazilian and Italian beans cvs. also observed high TPC and antioxidant capacities (Estrada-Girón et al, 2005;Han et al, 2007).…”
Section: Nutritional Qualitymentioning
confidence: 79%
“…In other studies, Carbanaro, Cappelloni, Nicoli, Lucarini, & Carnovale, 1997 reported that while cooking improved in vitro digestibility of chickpea and common bean flour/concentrates, it did not increase the digestibility of faba bean and lentil flour. Differences clearly exist in the digestibility and nutritional quality of different pulses and the factors influencing digestibility can vary (Han, Swanson, & Baik, 2007;Yasmin, Zeb, Khalil, Paracha, & Khattak, 2008). Further studies on the digestibility of pulse flours, protein concentrates and protein isolates as a function of different processes and processing conditions would, therefore, be very useful.…”
Section: Protein Digestibilitymentioning
confidence: 99%